This preview shows page 1. Sign up to view the full content.
Unformatted text preview: x = 2 , we get f ( 2 ) = e 2 1 2 (1 + ln(1) + 2 1 ) = e 2 . Solution 2: Take logarithms of both sides of y = e x (sin x ) x , to get ln y = ln( e x (sin x ) x ) = ln( e x ) + ln((sin x ) x ) = x + x ln(sin x ) . Now take derivatives of both sides to get 1 y y = 1 + ln(sin x ) + x cos x sin x . Multiplying both sides by y = e x (sin x ) x gives exactly the same derivative formula as in solution 1, and the rest follows indentically. 1...
View Full
Document
 Spring '08
 WILKENING
 Math, Calculus

Click to edit the document details